2013
DOI: 10.1016/j.vaccine.2013.08.062
|View full text |Cite
|
Sign up to set email alerts
|

Standard method for detecting upper respiratory carriage of Streptococcus pneumoniae: Updated recommendations from the World Health Organization Pneumococcal Carriage Working Group

Abstract: In 2003 the World Health Organization (WHO) convened a working group and published a set of standard methods for studies measuring nasopharyngeal carriage of Streptococcus pneumoniae (the pneumococcus). The working group recently reconvened under the auspices of the WHO and updated the consensus standard methods. These methods describe the collection, transport and storage of nasopharyngeal samples, as well as provide recommendations for the identification and serotyping of pneumococci using culture and non-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
427
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 399 publications
(442 citation statements)
references
References 132 publications
2
427
0
1
Order By: Relevance
“…The lytA gene is considered to be a specific molecular target for pneumococcus identification, where its restriction by BsaI provides in addition specific signatures for reliable diagnosis of S. pneumoniae infections, especially those caused by non-typeable strains [7]. Moreover, real-time PCR targeting lytA was recommended as a rapid and reliable non-culture assay to complement the gold standard culture technique for S. pneumoniae detection [8]. Nevertheless, a new study showed that misidentification of S. pneumoniae can occur [9].…”
Section: Introductionmentioning
confidence: 99%
“…The lytA gene is considered to be a specific molecular target for pneumococcus identification, where its restriction by BsaI provides in addition specific signatures for reliable diagnosis of S. pneumoniae infections, especially those caused by non-typeable strains [7]. Moreover, real-time PCR targeting lytA was recommended as a rapid and reliable non-culture assay to complement the gold standard culture technique for S. pneumoniae detection [8]. Nevertheless, a new study showed that misidentification of S. pneumoniae can occur [9].…”
Section: Introductionmentioning
confidence: 99%
“…The method presented here is viewed without oil-immersion and under 400X magnification 15,17 . This method is quick, simple and relatively easy to read 23 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this is minimized in the above protocol due to the small amount of antiserum used for each reaction. Several other methods have been described for serotyping pneumococci 23,24 . However, Quellung remains the gold standard and the development of new methods requires standardization against the Quellung reaction 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Standardized methodologies were used for collection, transportation and storage of the NPS and subsequent culturing, identification and isolation of S. pneumoniae 31, 32. Briefly, NPS were stored in 1 ml of skimmed milk–glucose–glycerol broth (SMGGB) at −70°C until further processing at the PNG Institute of Medical Research.…”
Section: Methodsmentioning
confidence: 99%